Insights Into Walnut Lipid Metabolism From Metabolome and Transcriptome Analysis - Yan, Suxian; Wang, Xingsu; Yang, Chenkang; Wang, Junyou; Wang, Ying; Wu, Bangbang; Qiao, Ling; Zhao, Jiajia; Mohammad, Pourkheirandish; Zheng, Xingwei; Xu, Jianguo; Zhi, Huming; et al. (Frontiers in Genetics, 2021)
The oil content of walnut kernel is an excellent source of essential fatty acids. Evaluating lipid of walnut systematically has great significance for the development of nutrition and function of walnut. An ultra performance liquid chromatography/orbitrap high resolution mass spectrometry (UHPLC-Orbitrap HRMS) was applied to characterize lipids of walnut. A total of 525 lipids were detected in walnut including 250 glycerides (GL), 221 phospholipids (GP), 36 sphingolipids (SP) and 18 saccharolipids (SL). Diacylglycerols (DG) and Triacylglycerols (TG) were the dominant components in glycerides. TG (18:2/18:2/18:3) was the main molecule in TG and DG (18:2/18:2) was the main molecule in DG. Essential fatty acids such as linoleic acid and linolenic acid were the main fatty acid chains in DG and TG. There were many kinds of phospholipids in walnut, including Phosphatidic acid (PA), Phosphatidylglycerol (PG), Phosphatidyl serine (PS), Phosphatidyl choline (PC), Phosphatidyl ethanolamine (PE), Phosphatidyl inositol (PI), Phosphatidylinositol diphosphate (PIP), Lyso- posphatidyl choline (LPC), Lyso-posphatidyl ethanolamine (LPE), Lyso-phosphatidylglycerol (LPG), Lyso-phosphatidyl inositol (LPI) and Cardiolipin (CL). Among them, the concentration of PA (5.58%) was higher. The lipid map and lipid metabolism pathway of walnut constructed in this research can provide a theoretical basis and gene targets for the functional development of walnut in order to increase oil content and modify fatty acid composition.